Impact of Capillarity-Induced Rising Damp on the Energy Performance of Residential Buildings in Makurdi, Benue State (Global Journals of Research in Engineering, 2026)
Moisture movement through building envelopes, particularly rising damp caused by capillarity, has long been recognized as a major factor influencing material durability, indoor comfort, and overall building performance. In humid tropical settings such as Makurdi Local Government Area (LGA), Benue State, this phenomenon is especially pronounced due to high groundwater levels, seasonal rainfall, and prevalent construction practices that often lack effective damp-proofing measures. This research investigates the relationship between capillarity-induced moisture in wall assemblies and the energy performance of residential buildings within Makurdi LGA. Employing a field-based methodology, the study combines in-situ measurements of wall moisture content, indoor thermal and humidity profiles, and cooling energy use with a survey of construction details, occupancy patterns, and maintenance histories. A comparative analysis between buildings with evident rising damp and those with minimal or no damp manifestations will be conducted to establish correlations between wall moisture indices and cooling energy demand.
Keywords: Building Pathology; Capillarity; Cooling Energy Demand; Energy Performance; Hygrothermal Behavior; Makurdi; Moisture in Buildings; Rising Damp; Sand Crete Walls; Tropical Architecture